Breast cancer patients' quality of life during chemotherapy at Royal Prima General Hospital - Saragih, Chanli; Lumbantobing, Christina J.R.E.; Chiuman, Linda; Sylvana, Dhini; Ibnu, Syahroni; Yuliansyah, Jeri; Iskandar, Ari Rahman (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Breast cancer is the most prevalent malignancy and a leading cause of cancer-related death among women worldwide. Chemotherapy, a primary treatment modality, often significantly impacts patient quality of life (QoL). This study aimed to analyze the QoL of breast cancer patients undergoing chemotherapy at Royal Prima General Hospital. Methods: We employed a descriptive-analytic cross-sectional design with a purposive sample of 51 patients. Data were collected using a respondent characteristics form and the validated Indonesian version of the WHOQOL-BREF instrument. Results: Results indicated the majority of respondents were aged 36-60 years (86.3%), married (100%), had a junior high school education (49%), and had a disease duration of 1-24 months (82.4%). Overall QoL for most patients was moderate (60.8%), followed by good (35.3%) and poor (3.9%). Cross-tabulation analysis revealed varied QoL distribution across age, marital status, education, disease duration, and cancer stage. Conclusion: We conclude that the QoL of breast cancer patients undergoing chemotherapy at Royal Prima General Hospital is predominantly at a moderate level, indicating a need for focused attention on psychosocial support, health education, and symptom management to holistically improve patient well-being during treatment.